THE COVID-19 VULNERABILITY IN ASSOCIATION WITH ABO AND RH BLOOD GROUP SYSTEM: AN ANALYTICAL STUDY WITH REVIEW OF LITERATURE - DEVENDRAPPA, PRIYADARSHINI; VARADHARAJ, LATHA; ANANTHARAJ, JYOTHI; H K, JAYASHREE; BHOWMIK, PARAMITA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: COVID-19 began on March 11, 2020, when the WHO declared a pandemic, caused by the novel coronavirus. At present, millions of COVID-positive cases are reported with an increase in mortality during the second wave. There are various studies and research chronicles available regarding hematology and biochemical criteria in COVID-19 infection. On the other hand, there is an urge to explore of ABO blood group vulnerability of COVID-19-infected patients in our study population. Our aim of this study is to scrutinize the relevance between the ABO, Rh blood types, and the susceptibility to COVID-19 and to study the capable use of the ABO blood group system for risk stratification of COVID-19. Methods: ABO and Rh grouping data available of 500 COVID-19 positive were collected from our hospital blood bank. Data about the age and gender of each patient are obtained from the Laboratory Information system. The patients who were confirmed to have SARS-CoV-2 infection by RT-PCR and ABO and Rh typing data available are included in the study. Results: The ABO blood group in 500 people in tertiary care hospital displayed a percentage distribution of 31.8%, 27.4%, 6.4%, and 34.4% for A, B, AB, and O, respectively. The proportion of non-O blood group (A, B, and AB) among patients with COVID-19 was substantially higher compared to the O blood group. Conclusion: This study reports an association between COVID-19 susceptibleness and the ABO blood group system. Categorically, non-O blood group systems have a greater risk compared to the O blood group system and have a higher risk of ICU admissions due to COVID-19-related complications.